2014
DOI: 10.1128/aem.00739-14
|View full text |Cite
|
Sign up to set email alerts
|

Purine Biosynthesis, Biofilm Formation, and Persistence of an Insect-Microbe Gut Symbiosis

Abstract: cThe Riptortus-Burkholderia symbiotic system is an experimental model system for studying the molecular mechanisms of an insect-microbe gut symbiosis. When the symbiotic midgut of Riptortus pedestris was investigated by light and transmission electron microscopy, the lumens of the midgut crypts that harbor colonizing Burkholderia symbionts were occupied by an extracellular matrix consisting of polysaccharides. This observation prompted us to search for symbiont genes involved in the induction of biofilm format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 47 publications
0
51
2
1
Order By: Relevance
“…Because A. phagocytophilum colonization reduced the abundance of Gram-positive biofilm-forming species like the Enterococci, we hypothesized that IAFGP alters the tick microbiota by inhibiting bacterial biofilms in the gut. Biofilms have been demonstrated to serve important roles in facilitating pathogen colonization in arthropod intestines (12)(13)(14). To elucidate the importance of IAFGP in shaping the tick gut microbiota, we injected the antibiofilm peptide, P1, derived from IAFGP (25), and showed that this improved A. phagocytophilum infection, in ticks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because A. phagocytophilum colonization reduced the abundance of Gram-positive biofilm-forming species like the Enterococci, we hypothesized that IAFGP alters the tick microbiota by inhibiting bacterial biofilms in the gut. Biofilms have been demonstrated to serve important roles in facilitating pathogen colonization in arthropod intestines (12)(13)(14). To elucidate the importance of IAFGP in shaping the tick gut microbiota, we injected the antibiofilm peptide, P1, derived from IAFGP (25), and showed that this improved A. phagocytophilum infection, in ticks.…”
Section: Discussionmentioning
confidence: 99%
“…In arthropods, the microbiota is associated with a biofilm, generated from diverse bacterial species. These microbial biofilms are necessary for establishing successful symbiotic relationships with their arthropod hosts (12)(13)(14).…”
mentioning
confidence: 99%
“…When host insect fitness and developmental rates were compared between insects harboring Burkholderia gut symbiont and Burkholderia-absent apo-symbiont insects, the beneficial consequences were observed on the host insect by the presence of gut symbiont [4]. These features of the Riptortus-Burkholderia gut symbiotic system provided good opportunities to study insect symbiosis at molecular and biochemical levels [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm formation has been reported in other Burkholderia species (Burkholderia pseudomallei and B. cepacia complex species), and it may be associated with many factors, such as nutrient content, osmolarity, oxygen, pH, and temperature (49)(50)(51). In selected microbe-invertebrate symbioses, biofilm formation contributes to the establishment and persistence of symbiotic bacteria in host symbiont organs (52)(53)(54)(55). Biofilms produced by crypt-associated exocellular Burkholderia spp.…”
Section: Discussionmentioning
confidence: 99%